(untitled) (Research, Society and Development, 2023)
Introduction: Maranhão has the highest incidence of penile neoplasms in the world, a pathology diagnosed more frequently in men with low socio-educational level, with poor hygiene habits and from developing countries. Thus, it is essential to understand the epidemiological aspects that justify these data. Objective: to identify the epidemiological aspects, risk factors and treatment of penile neoplasms in men from Maranhão. Methods: This work is a systematic review of the literature, developed according to PRISMA, in which 09 articles were selected, provided that they answered the guiding question, elaborated through the PICO strategy, having the following inclusion criteria: articles published in English, between 2017 and 2022, in the PUBMED and BVS databases. The Boolean characters “AND” and “OR” were used, with DeCS descriptors: penile neoplasms, health policy, male urological surgical procedures, men’s health. Results: the following risk factors were found: poor penile hygiene; phimosis; unprotected sex with multiple partners; HPV infection; low income; live/work in the rural area; low or no education; be married or in a stable relationship; practice zoophilia. As for treatment, lymphadenectomy, chemotherapy, radiotherapy and penectomy have been the techniques used and indicated according to the degree of involvement: penile; and lymph node, whether inguinal or pelvic. Conclusion: it is imperative that public health policies are implemented in order to deal with sociocultural issues in locations with a high incidence of penile neoplasia, thus effectively acting in favor of awareness and reversal of these indicators.